The minimizer for the second order diﬀerential problem with the integral condition - Paukštaitė, Gailė (Lietuvos matematikos rinkinys, 2019)
In this paper, we investigate the best ﬁt solution for the second order diﬀerential problem with one initial and other integral conditions. We obtain the representation of that minimizer and present an example.paration.
Keywords: integral condition; least squares solution; Moore–Penrose inverse; minimizer